Differential protein expression in Colletotrichum acutatum : changes associated with reactive oxygen species and nitrogen starvation implicated in pathogenicity on strawberry - Brown, S.H.; Yarden, O.; Gollop, N.; Chen, S.; Zveibil, A.; Belausov, E.; Freeman, S.
The cellular outcome of changes in nitrogen availability in the context of development and early stages of pathogenicity was studied by quantitative analysis of two-dimensional gel electrophoresis of Colletotrichum acutatum infecting strawberry. Significant alterations occurred in the abundance of proteins synthesized during appressorium formation under nitrogen-limiting conditions compared with a complete nutrient supply. Proteins that were up- or down-regulated were involved in energy metabolism, nitrogen and amino acid metabolism, protein synthesis and degradation, response to stress and reactive oxygen scavenging. Members belonging to the reactive oxygen species (ROS)scavenger machinery, superoxide dismutase and glutathione peroxidase, were up-regulated at the appressorium formation stage, as well as under nitrogen-limiting conditions relative to growth with a complete nutrient supply, whereas abundance of bifunctional catalase was up-regulated predominantly at the appressorium formation stage. Fungal ROS were detected within germinating conidia during host pre-penetration, penetration and colonization stages, accompanied by plant ROS, which were abundant in the apoplastic space. Application of exogenous antioxidants quenched ROS production and reduced the frequency of appressorium formation. Up-regulation in metabolic activity was detected during appressorium formation and nutrient deficiency compared with growth under complete nutrient supply. Enhanced levels of proteins related to the glyoxylate cycle and lipid metabolism (malate dehydrogenase, formate dehydrogenase and acetyl-CoA acetyltransferase)were observed at the appressorium formation stage, in contrast to down-regulation of isocitrate dehydrogenase. The present study demonstrates that appressoria formation processes, occurring under nutritional deprivation, are accompanied by metabolic shifts, and that ROS production is an early fungal response that may modulate initial stages of pathogen development.